Spontaneous choledochoduodenal fistula with tuberculous duodenal ulceration - Karthikeyan, VS (Ann R Coll Surg Engl, 2014)
Spontaneous choledochoduodenal fistulas (CDFs) are rare. The most common aetiology is penetrating duodenal ulcers, observed in 80% of cases. Even in areas where acid peptic disease is common, tuberculosis should be considered as a cause, especially in developing countries like India, where tuberculosis is common. The management of CDF due to acid peptic disease is predominantly surgical while healing of tuberculous CDF has been reported with antitubercular treatment. A preoperative diagnosis of tuberculous CDF by endoscopic biopsy from the duodenal ulcer or image guided fine needle aspiration if abdominal lymph nodes are present can eliminate the need for surgery and achieve a cure with antitubercular treatment. The CDF in this case was due to caseation of periduodenal lymph nodes rupturing into the duodenum and the bile duct.